2017
DOI: 10.1016/j.xphs.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endogenous Biomarkers to Predict the Propensity of Drug Candidates to Cause Hepatic or Renal Transporter-Mediated Drug-Drug Interactions

Abstract: Drug transporters expressed in liver and kidney play a critical role in the elimination of a wide range of drugs and xenobiotics and inhibition of these transporters may therefore cause clinically significant drug-drug interactions (DDIs). Currently, in vitro transporter inhibition data are used to assess the risk that a drug candidate may act as an inhibitor of a transporter in patients at clinically relevant exposures. However, this approach is hampered by low confidence in in vitro to in vivo extrapolations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 97 publications
(143 reference statements)
1
71
0
Order By: Relevance
“…Recently, endogenous biomarkers of drug transporters have gained more interest from both industry and academia with a potential to replace or assist in prioritization of a dedicated DDI study and thus offering cost and time effectiveness. Multiple endogenous biomarkers of OATP1B1/1B3 have been suggested/proposed, including coproporphyrin I and III, conjugated and unconjugated bilirubin, conjugated metabolites of steroids, conjugated and unconjugated bile acids, fatty acid dicarboxylates tetradecanedioate and hexadecanedioate, thyroid hormones and their metabolites, and so on . Coproporphyrin I and III, which are porphyrin metabolites arising from heme synthesis, were recently reported to be the reasonable endogenous biomarkers correlating with OATP1B function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, endogenous biomarkers of drug transporters have gained more interest from both industry and academia with a potential to replace or assist in prioritization of a dedicated DDI study and thus offering cost and time effectiveness. Multiple endogenous biomarkers of OATP1B1/1B3 have been suggested/proposed, including coproporphyrin I and III, conjugated and unconjugated bilirubin, conjugated metabolites of steroids, conjugated and unconjugated bile acids, fatty acid dicarboxylates tetradecanedioate and hexadecanedioate, thyroid hormones and their metabolites, and so on . Coproporphyrin I and III, which are porphyrin metabolites arising from heme synthesis, were recently reported to be the reasonable endogenous biomarkers correlating with OATP1B function .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple endogenous biomarkers of OATP1B1/1B3 have been suggested/proposed, including coproporphyrin I and III, conjugated and unconjugated bilirubin, conjugated metabolites of steroids, conjugated and unconjugated bile acids, fatty acid dicarboxylates tetradecanedioate and hexadecanedioate, thyroid hormones and their metabolites, and so on. [16][17][18][19] Coproporphyrin I and III, which are porphyrin metabolites arising from heme synthesis, were recently reported to be the reasonable endogenous biomarkers correlating with OATP1B function. 18 A 5-to 6-fold increase in concentration of coproporphyrin I and III was observed after administration of rifampin (as a strong OATP1B inhibitor in humans), 18 suggesting their utility in capturing potent DDIs mediated by OATP1B1/1B3 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important knowledge gaps in interpreting kinetic profiles of endogenous biomarkers is the involvement of other elimination pathways, such as other transporters or biotransformation. For CPI, MRP2 is likely involved in the elimination, as suggested from in vitro studies and altered kinetic profiles in patients with Dubin‐Johnson syndrome (genetically linked disease with MRP2 deficiency) or subjects with ABCC2 polymorphisms . It has implications on the inhibition potencies from clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…For CPI, MRP2 is likely involved in the elimination, as suggested from in vitro studies 22,23 and altered kinetic profiles in patients with Dubin-Johnson syndrome (genetically linked disease with MRP2 deficiency) or subjects with ABCC2 polymorphisms. 24 It has implications on the inhibition potencies from clinical data. It is difficult, however, to quantify the contribution of MRP2 to overall elimination of CPI, because MRP2 is expressed in multiple organs, including the liver, kidneys, and intestines.…”
Section: Aucr Of Pravastatinmentioning
confidence: 99%
“…A recent study showed that CPI and CPIII can successfully predict strong and mild OATP1B‐mediated DDI in the clinic (Kunze, Ediage, Dillen, Monshouwer, & Snoeys, ). For detailed information on transporter biomarkers, please refer to other articles on the topic (Barnett et al, ; Chu et al, ; Chu, Chan, & Evers, ; Jones et al, ; Mariappan, Shen, & Marathe, ; Mueller, Sharma, Koenig, & Fromm, ; Rodrigues & Rowland, ; Shen, ; Yoshikado et al, ). Biomarkers are active research areas and future advances will help to provide new tools and insights to more accurately predict clinical DDIs.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%